Development of Hydroxyapatite Carbon Modified Electrode (HAP-CME) for Drug Detection - Masing, Phil Foster (Universiti Teknologi Petronas, 2011)
Drug abuse is a global issue and it exist in both developed and developing countries. The conventional quantitative drug detection system has long detection time, complex operations, expensive, bulky, and not portable. Thus, an alternative, green in-situ detection system is needed. Voltammmetry holds a great opportunity to be used as alternative for quantitative drug detection method due to its simplicity and accuracy. It has been reported that hydroxyapatite Carbon Modified Electrode (HAP-CME) has excellent electrocatalytical response and low detection limit in voltmammetry in the trace analysis of hazardous material. However, the usage HAP-CME in drug analysis has not been reported yet. In this paper, Ascorbic Acid (AA) is used as a drug. HAP-CME was fabricated by mixing Hydroxyapatite to the carbon paste mixture. As compared to the normal Carbon Paste Electrode (CPE), HAP-CME possesses good electrical conductivity, excellent sensitivity, and better electron transfer kinetics towards the standard redox couple of Fe(CN)63-/4- . Then, HAP-CME was further used for the detection AA and a successful result is obtained. HAP-CME exhibited an excellent electrocatalytical response towards the redox reaction of AA with lower detection limits and great sensitivity.